Lelang Benda Jaminan Hak Tanggungan Akibat Wanprestasi Perspektif Hukum Nasional Dan Hukum Islam - Putriana; Azman (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2022)
The main problem in this research is related to the existence of problems regarding the auction of mortgage guarantee objects due to defaults that occur in the community so it is necessary to know how National Law and Islamic Law view this matter. The main problem is then broken down into several sub-problems or research questions, namely: 1.) How to determine objects that can be used as collateral for mortgages? (2) How is the auction process for mortgage guarantees from a national legal perspective? (3) What is the process of auctioning mortgage collateral from an Islamic legal perspective? The type of research used in this research is library research (Library Research). The approach used is descriptive-comparative. Techniques in analyzing data deductively, namely the pattern of studies discussed and studied are general-specific. The results of this study indicate that objects that can be used as collateral for mortgage rights include: property rights, use rights, building rights, and use rights on state land. Auction of collateral rights from a national legal perspective, namely the Act has guaranteed legal certainty for auction buyers which is clearly stated in the Vendu Reglement, HIR, and PMK Number 106/PMK.06/2013 concerning Amendments to PMK Number 93/PMK.06/ 2010 and PMK No. 93/PMK.06/2010, then revised again with the Minister of Finance Regulation No. 213/PMK.06/2020 concerning Auction Implementation Guidelines. Meanwhile, the auction of collateral objects from the perspective of Islamic law, namely buying and selling auctions (muzayyadah) in Islamic law is permissible, namely the agreement of scholars about the permission of buying and selling by auction and has even become a prevailing custom in the Muslim market in the past. The implication of this research is that auction as an alternative way of selling goods is a sales system that has been known for a long time. Meanwhile, auctions in Indonesia have been known since 1908 with the issuance of the Vendu Reglement (Statusblad Auction Rules of 1908 Number 189 as amended by Staatsblad of 1940 Number 56). In accordance with developments in the implementation of the auction, a decree of the minister of finance and a decision of the Director General of Receivables and State Auctions shall be issued